Formação, saberes e práticas : experiências no contexto da pesquisa-intervenção com professores de educação física da rede pública de Sergipe - Santos, Mateus Henrique Silva (2021)
This research aims to analyze skills and practices (re)constructed by Physical Education teachers from public schools in Sergipe, with regards to the identification of interrelationships established in their initial and continuing educational pathways. The experience mobilizes different dimensions that make up teaching practices and it also produces reflections geared towards the appropriation of reality as wells as significant learning and teaching processes. This study is based on the theory of complexity found in the ground aspects of ontology and axiology through the intersubjective relationships of the subjects, which were permeated by multi-dimensions and plural views that involve distinct structures of human thought and action. Regarding the nature of the data, this is a qualitative study that involves 38 teachers of Physical Education curriculum component. This investigation is also supported by the principles of intervention research that considers the implications of the researcher in the production of knowledge. The data construction took place in a formative itinerary that was organized in interactive modules through asynchronous activities and synchronous meetings. The devices selected for the analysis were educational memories, forms and questionnaires that were (re)grouped in semantic basins guided by cognitive operations in a movement of coming and going, which resulted in the following subsuming notions: eco-formative processes, transdisciplinary experiences, senses and meanings of teaching. The results allow us to infer that the teachers immersed in this research interpret their (self) formative trajectories by involving themselves, the others and the world. Furthermore, the findings highlighted the relevance of mobilizing actions and skills to articulate theory-practice in order to overcome the reproduction, fragmentation and disjunction of knowledge. Regarding the experiences of in-service continuing education, reflections on educational praxis revealed (re)signified learning in the field of creative processes, the appropriation of interactive interfaces and applicability of active methodologies as a way to enhance Physical Education classes and make students as protagonists of their learning processes.